A Study Of Digital Record Storage Management Institutions In Art Archive Indonesian Visual Art Archive - Akbar, Muhammad; Winoto, Yunus; Rohanda, Rohanda (D3 Teknisi Perpustakaan Fakultas Vokasi Universitas Airlangga, 2017)
This study aims to determine the digital archive storage management conducted Indonesian Visual Art Archive which includes the acceptance stage archive, metadata archives, archive conversion, digital archive storage, retrieval and archive and archive evaluation stage. The location of this research done in archives art Yogyakarta Indonesian Visual Art Archive. The method used in the study used a qualitative approach with case study. As for the technique of data collection is done through observation, interview and literature study. Based on the results of this research note that the digital archive management activities undertaken archives art Yogyakarta Indonesian Visual Art Archive is a form of awareness of the importance of art as archive footage of historical development and culture. As for the digital archive management activities are some steps being taken begins with the acceptance of the archive, metadata archives, archive conversion, digital archive storage, retrieval and archive and archive evaluation stage. In this digital archive management does not have a cycle of destruction of records for each archive is a work of art performers. In addition, the digital archive storage management activities in archives art Yogyakarta Indonesian Visual Art Archive is supported by a clear procedural system.